Food Security and the Role of Biotechnology (Bangladesh Journal of Nutrition, 2021)
Biotechnological approaches are given a greater significance as they continue to show promising potential to facilitate food security. These biotechnologies may consist of manipulation and interference in plant breeding (Marker-assisted plant breeding, mutational breeding) genetically manipulating the crop themselves (GM foods), or even just influencing the environmental factors to bring about the desired changes in the crop production (use of bio-fertilizers and bio-pesticides).Some of the greater benefits such as, increased crop yield, enhanced nutritional quality, upgraded ability to adapt and survive, and lengthened shelf-life brought about by these techniques are making developing countries including Bangladesh lean heavily towards the increased commercialization of biotech crops. Even amidst strong oppositions and a few limitations, the popularity of Bt brinjal and the continual development of many biotech rice varieties in Bangladesh alone, further substantiate the favourability of biotech crops and their potential to better the situation favouring both the environment and the economy.Bangladesh J. Nutr. Vol. 34, December 2020, P: 01-13